A política do nome próprio no Plano de Ações Articuladas - MT - Soares, Gracielle Gomes (2012)
This work is aligned to the philosophy of education’s research field, it operates concepts arising from readings of Philosophy, held at GEDFFE - Studies and Research Group in Philosophy, Didactic and Teacher Education. The philosophical base that promotes works on education at GEDFFE and, therefore mine, is drawn primarily from the readings of Friedrich Wilhelm Nietzsche, Jacques Derrida, Gilles Deleuze and Michel Foucault. This research aims to bring a public education policy’s play called Articulated Actions Plan – PAR, based on a double derridean concept: the proper noun politics and signature. The first chapter presents the life and works of the central reference of this research: Friedrich Nietzsche and Jacques Derrida, as well as the concepts that involve them and have become the conceptual analysis basis of this work. In the second chapter: PAR and the play of public policies, presents the Articulated Actions Plan – PAR, understanding that the play of a proper noun policy is present in its composition, since it features a declarative act responsible of an institution foundation, and a supposedly signed name. It also brings the PAR in the national context as one of the bases of the Brazil’s Education Development Plan – PDE, launched in 2007, and, subsequently, how PAR was developed and executed in the state of Mato Grosso. As we give a high importance to the usage of names in our research, a name that has signed an engaged in its works, it is presented in this chapter the names of the selected Secretary of Education, accompanied by a brief information of their cities and a summary of the PAR diagnosis carried outbetween the years of 2007 and 2008, according to a public report available at the Integrated Monitoring and Control Execution Module – SIMEC - PAR. In the third and final chapter: The text as a creative act, I dedicate myself to the work of a conceptual analysis of the narratives of seven municipal educational secretaries of the state of Mato Grosso, based on the derridean concepts. At this stage, the concepts take an artistic and body intonation center. They are plastic, flexible, fond of me. The proper noun policy and signature are born with Derrida, but they are shaped by my writings, since there is a play, an institutional scene in my recreation. By telling me from the text of the secretaries, I do no interpretative analysis, because I do not operate inferences, I just tell what was said to me. What I present through the proper noun policy concept and signature, is that even when a person talks about what it is not her or him, it is making a policy of its name – a proper noun policy.